The Byzantine and Early Islamic near East - King, Geoffrey.
1 online resource (333 pages)
Keywords: This volume revisits archaeological evidence from Syria, Palestine, the Arabian Peninsula, Iraq and Egypt describing a variety of land-use patterns and the development of a particular type of settlement across the Near East._x000B_1. Pierre-Louis Gatier, Villages du Proche-Orient protobyzantin (4ème-7ème s.): Étude régionale _x000B_2. Henry Innes Macadam, Settlements and Settlement Patterns in Northern and Central Transjordania, c. 550 - c. 750_x000B_ 3. Yoram Tsafrir and Gideon Foerster, From Scythopolis to Bays n - Changing Concepts of Urbanism _x000B_4. Ali Zeyadeh, Settlement Patterns: An Archaeological Perspective. Case Studies from Northern Palestine and Jordan _x000B_5. Robert Schick, The Settlement Pattern of Southern Jordan: The Nature of the Evidence _x000B_6. Donald Whitcomb, The Misr of Ayla: Settlement at al-'Aqaba in the Early Islamic Period _x000B_7. George T. Scanlon, Al-Fust t: The Riddle of the Earliest Settlement_x000B_8. G. R. D. King, Settlement in Western and Central Arabia and the Gulf in the Sixth-Eighth Centuries A.D. _x000B_9. Mikhail B. Piotrovsky, Late Ancient and Early Mediaeval Yemen: Settlement Traditions and Innovations _x000B_10. Michael G. Morony, Land Use and Settlement Patterns in Late Sasanian and Early Islamic Iraq _x000B_11. Alastair Northedge, Archaeology and New Urban Settlement in Early Islamic Syria and Iraq _x000B_“This volume presents a much needed addition to the history of the transit from Byzantine to Islamic administration _x000B_and a welcome survey of recent archaeology of an understudied period“ (Gladys Frantz-Murphy).